A Psychological Analysis of Iranian Infertile Couples' Attitudes Toward Gestational Surrogacy: A Cross‐Sectional Study - Masoumeh Esmaeilivand; Arezoo Haseli; Alirez Karampour; Alireza Khatony; Shahab Rezaeian; Amirhossein Naghibzadeh; Mohammad Mehdi Mohammadi (Health Science Reports)
ABSTRACT Background and Aims In the last two decades, assisted reproductive technologies (ARTs), such as surrogacy, have helped couples address infertility. However, the use of these techniques can present moral, social, and psychological challenges for both the infertile parents and the surrogate mother. Therefore, this study investigates the attitudes of infertile couples toward surrogacy and the associated challenges. Methods This cross‐sectional survey was conducted on 176 infertile couples. Data were collected using a bifurcated questionnaire that assessed the challenges and concerns of infertile couples regarding surrogacy. The data were analyzed using SPSS version 22 statistical software. Results The average attitude score toward surrogacy was 92.93 ± 4.89, with no significant differences between females and males. The results of the five distinct subscales indicated that with increasing education levels, intentional attitudes and future perspectives on surrogacy decreased (b = −0.59, p = 0.02) and the score for children born through surrogacy decreased significantly (b = −0.60, p = 0.04). Additionally, there was a significant relationship between the history of ART and the overall acceptance of surrogacy (b = 1.6, p = 0.002). Conclusion These findings are important as they highlight the attitudes of infertile couples in Iranian society toward surrogacy. It appears that providing adequate education to society will significantly facilitate the optimal use of this treatment method.